2005
DOI: 10.1016/j.jvs.2005.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Type IV thoracoabdominal aortic aneurysm with lymphoplasmacytic aortitis and cystic medial degeneration in a 32-year-old patient with Marfan syndrome

Abstract: Aortitis identified in approximately 12% of all thoracoabdominal aneurysms. The most common subtype of inflammatory aortitis is giant cell aortitis, followed by lymphoplasmacytic aortitis. Inflammatory aortitis may occur in isolation or as part of a systemic inflammatory disorder such as Takayasu arteritis, systemic lupus erythematosus, rheumatoid arthritis, and giant cell arteritis. Aortitis has not been described in patients with Marfan syndrome. We report the case of a 32-year-old man with Marfan syndrome a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…The presence of both FBN1 ‐associated familial thoracic aortic aneurysm and dissection (FTAAD) and IgG4‐RD in the one person most likely represents a chance association, as we have found only one other example: Lindsay et al (2016) reported a case of IgG4‐related chronic peri‐aortitis and coeliac disease in a man with MFS. However, we know of two other reports that may be relevant: Chong and al‐Kutoubi (Chong & al‐Kutoubi, 1991) reported two cases of MFS with aortic aneurysms and retroperitoneal fibrosis, and Cordera, Bowen, Aubry, and Gloviczki (2005) reported a case of MFS with thoracoabdominal aneurysm with lymphoplasmacytic aortitis. In rare instances, the presence of altered fibrillin‐1 may predispose to an immune response of the type seen in IgG4‐RD.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of both FBN1 ‐associated familial thoracic aortic aneurysm and dissection (FTAAD) and IgG4‐RD in the one person most likely represents a chance association, as we have found only one other example: Lindsay et al (2016) reported a case of IgG4‐related chronic peri‐aortitis and coeliac disease in a man with MFS. However, we know of two other reports that may be relevant: Chong and al‐Kutoubi (Chong & al‐Kutoubi, 1991) reported two cases of MFS with aortic aneurysms and retroperitoneal fibrosis, and Cordera, Bowen, Aubry, and Gloviczki (2005) reported a case of MFS with thoracoabdominal aneurysm with lymphoplasmacytic aortitis. In rare instances, the presence of altered fibrillin‐1 may predispose to an immune response of the type seen in IgG4‐RD.…”
Section: Discussionmentioning
confidence: 99%